The ability of orthodontists and laypeople in the perception of gradual reduction of dentogingival exposure while smiling - Elaine Cristina da Silva Barros; Marielly Damiana Oliveira de Carvalho; Karina Corrêa Flexa Ribeiro Mello; Patrícia Botelho; David Normando (Dental Press Editora, 2012)
OBJECTIVE: To assess differences in how orthodontists and laypersons perceive a reduction in dentogingival display on smiling. METHODS: Sixty examiners from both genders (30 laypersons and 30 orthodontists) evaluated photographs of spontaneous smiles of two subjects , one male and one female. Based on the original images, smile height was modified by means of an image manipulation software program. The examiners assigned scores ranging from 0 to 10, according to the level of pleasantness. Method reproducibility was examined using the Wilcoxon test, while the Friedman and Wilcoxon tests (p < 0.05) were employed to observe intra- and interexaminer differences, respectively. RESULTS: No differences were found between the groups of examiners - in terms of esthetics - in response to changes in smile height of both genders . However,men smile had lower acceptability than the women smile. A mild reduction in dentogingival display on smiling (2 mm) was not perceived by either laypersons or orthodontists (p > 0.05). CONCLUSIONS: women smiles achieved higher scores than men smiles however, samples involving a larger number of subjects in each group are required to ensure whether or not this finding is linked to the subjects gender. OBJETIVO: avaliar a diferença na percepção de ortodontistas e leigos quanto à redução da exposição dentogengival no sorriso. MÉTODOS: no total, 60 avaliadores de ambos os sexos (30 leigos e 30 ortodontistas) avaliaram fotografias do sorriso espontâneo de dois indivíduos, um do sexo masculino e um do feminino. A partir das imagens originais, a altura do sorriso foi modificada usando-se um programa de manipulação de imagens. Os examinadores emitiram notas de 0 a 10, conforme o nível de agradabilidade. A reprodutibilidade do método foi examinada através do teste de Wilcoxon, enquanto os testes de Friedman e Wilcoxon (P<0,05) foram utilizados para observar as diferenças intra e interexaminadores, respectivamente. RESULTADOS: os resultados demonstraram não haver diferença entre os grupos de avaliadores com relação à estética quando a altura de ambos os sorrisos foi modificada. Entretanto, o sorriso do indivíduo do sexo masculino teve menor aceitabilidade do que o sorriso feminino. Uma suave redução na exposição dentogengival no sorriso (2mm) não foi percebida por leigos ou ortodontistas (p>0,05). CONCLUSÃO: o sorriso do indivíduo do sexo feminino recebeu notas mais altas do que o do masculino; entretanto, amostras envolvendo um maior número de indivíduos em cada grupo são necessárias para confirmar se a observação estaria relacionada ao sexo do indivíduo examinado.